(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article investigates how the English language contributes to reshaping the cultural identity of Uzbek-speaking individuals, especially within urban environments. The research highlights how English serves not only as a practical tool of communication but also as a cultural symbol linked to modernity, globalization, and social prestige. Drawing on sociolinguistic theory and qualitative observations, the paper discusses the motivations behind the adoption of English in daily interactions, media consumption, and education. It emphasizes the transformation of cultural values, identity perceptions, and generational differences resulting from this linguistic influence. Ultimately, the article argues that English is increasingly perceived as a medium of empowerment and cultural hybridity among urban Uzbeks.